Anisotropic Photonics Topological Transition in Hyperbolic Metamaterials Based on Black Phosphorus - Su, Zengping (Nanomaterials (Basel), 2020)
Based on in-plane anisotropy of black phosphorus (BP), anisotropic photonics topological transition (PTT) can be achieved by the proposed hyperbolic metamaterials structure, which is composed of alternating BP/SiO(2) multilayer. Through effective medium theory and calculated iso-frequency contour, PTT can be found by carefully choosing the incident plane and other parameters. With the finite element method and transfer matrix method, a narrow angular optical transparency window with angular full width at half maximum of 1.32° exists at PTT. By changing the working wavelength, thickness of SiO(2), or electron doping of black phosphorus, the incident plane of realizing PTT can be modulated, and anisotropic PTT is achieved.